2015
DOI: 10.1111/1756-185x.12701
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia: epidemiology and risk factors, a population-based case-control study in Lebanon

Abstract: This was the first study to address the epidemiology of FM in Lebanon and the region. The chronic nature of FM that is characterized by frequent bouts of intense disabling pain and symptoms constitutes a significant health and economic burden. Clustering of cases in coastal areas was partially explained by other factors such as body mass index, distress level, smoking and work status. The high burden of FM found in our study calls for further investigation of potential risk factors of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
2
10
2
Order By: Relevance
“…The characteristic features of the FM patients are in agreement with other studies that showed a positive family history and smoking. [ 22 23 ] These observations indicate that FM is a disease that related to the genetic disorder, and the smoking behavior is a reaction to stress. The values of MPV and platelet width distribution were significantly higher in FM patients than healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic features of the FM patients are in agreement with other studies that showed a positive family history and smoking. [ 22 23 ] These observations indicate that FM is a disease that related to the genetic disorder, and the smoking behavior is a reaction to stress. The values of MPV and platelet width distribution were significantly higher in FM patients than healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was made in a study conducted in Lebanon, as all FM cases were previously misdiagnosed and did not receive a diagnosis of FM. [13] The diagnosis of FM requires the efforts of patients to seek medical care and clinicians who are familiar with the disease and are willing to make the diagnosis, as FM diagnosis is confounded by drug-seeking behavior and malingering. [31] Our study shows that females have greater odds to have FM (OR=1.7), which goes in line with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Our study shows that females have greater odds to have FM (OR=1.7), which goes in line with the literature. [9,[11][12][13] Having health insurance is shown to be a risk factor in our population, probably because health insurance is not common in Syria, as only 14.1% of our sample have it. In addition, this insurance is offered to the workers in the public sector that have low wages due to economical in ation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the age of patients with FM Moukaddem et al (2017), they found that 58.8% of the sample (20 patients) were between 30 and 49 years old, while 29.4% (10 patients) were > 50 years (Moukaddem et al, 2017). The data of this study support the figures described in relation to the prevalence of FM in different age groups, the majority being between 49-58 years, followed by the group between 39-58 years (McNally, Matheson, & Bakowsky, 2006;Moukaddem et al, 2015;Queiroz, 2013).…”
Section: Discussionmentioning
confidence: 99%